Options on futures : - Summa, John F. (John Wiley & Sons, 2002)
Increased marketplace volatility and the expanding size of capital markets have led to an explosion of interest in options on futures. What makes these instruments so attractive is that they allow traders to profit from movements in the markets using little up-front capital and plenty of leverage. At the same time, they provide an excellent hedge against the risks associated with capital market investments. This book demystifies these notoriously difficult-to-understand instruments and provides state-of-the-art strategies and tools for making the most of options on futures.